Description of Enterobius (Colobenterobius) emodensis sp. n. (Nematoda: Oxyuridae) collected from Central Himalayan langur, Semnopithecus schistaceus, in Uttarakhand, India - Hasegawa, Hideo; Nautiyal, Himani; Sasaki, Mizuki; Huffman, Michael A. (Zootaxa, 2018)
A new pinworm species, Enterobius (Colobenterobius) emodensis sp. n. (Nematoda: Oxyuridae) is described from the Central Himalayan langur, Semnopithecus schistaceus, in Mandal Valley, Chamoli District, Uttarakhand, India, based on mature and immature adults and fourth-stage larvae. This species closely resembles Enterobius (Colobenterobius) zakiri parasitic in Tarai langur, Semnopithecus hector, recorded from Uttarakhand and Uttar Pradesh, India, but is readily distinguished by having a shorter esophagus and a shorter spicule. It is surmised that this pinworm has co-speciated with the host langur. The new species is also characterized in that the posterior 1/3 of the esophageal corpus is much darker. Phylogenetic analysis based on the sequences of partial Cox1 gene of mtDNA suggested a basal position of diversification of Colobenterobius from the Enterobius lineage.